Persepsi Mahasiswa terhadap Pemanfaatan Teknologi Artificial Intelligence (AI) dalam Memecahkan Masalah Matematika dan Membuat Karya Ilmiah - Tyaningsih, Ratna Yulis; Nourma Pramestie Wulandari; Dita Oktavihari (Griya Journal of Mathematics Education and Application, 2024)
This study aims to analyze students' perceptions of the use of Artificial Intelligence (AI) technology in solving mathematical problems and creating scientific papers. The study uses a descriptive quantitative method with data collection through questionnaires and semi-structured interviews. The subjects of the study consist of 58 active students from the University of Mataram who have experience using AI technology in completing their coursework assignments. The results of this study show that: 1) the majority of students (89.6%) feel that AI technology is easy to use, 2) 75,9% have confidence in the accuracy of this technology, 3) 94,9% experience increased efficiency in completing coursework assignments, and 4) based on interviews, concerns were found regarding the potential dependency on AI (29.3%) and ethical issues in its use (24.1%). This study emphasizes that AI can be an effective tool in education if used wisely. Therefore, policies are needed to support the ethical and responsible use of AI to ensure that students continue to develop critical thinking skills.